A comparative study of gaseous fuel flame characteristics for different bluff body geometries. (June 2022) - Ibrahim, I.A.; Shokry, A.H.; Shabaan, M.M.; Gad, H.M.
Abstract: Flame stabilization by a bluff-body is commonly used in many combustion applications to improve mixture characteristics, enhance flame stability and assist in combustion control. The main objectives of the present experimental work are concerned with studying the flame stabilization and combustion characteristics of Liquefied Petroleum Gas (LPG) with different bluff body shapes and sizes. An experimental test rig that consists of a gaseous fuel line, compressed air line, mixing chamber and burner is designed and constructed. Different bluff body shapes such as disc, cone, V-gutter, horizontal and vertical cylinders are used. The effects of different Blockage Ratios (B.R.) of 0.25, 0.35, 0.45, and 0.55 are studied at a constant equivalence ratio (Փ) of 1.85 for different bluff body shapes. The blowoff limits, temperature distributions, flame shapes, exhaust species concentrations and visible flame length are experimentally measured and discussed. The results indicated that increasing the blockage ratio leads to increasing the maximum flame temperature, increasing the flame diameter, and decreasing the flame length for all bluff body shapes. The centerline axial NO concentration has its peak values coincide with the maximum centerline axial temperatures. The flame using bluff body cone is more stable than using other bluff body shapes i.e., it has wide flammability limits or a wide range of operating conditions.